(untitled) (Praxis Educativa, 2023)
This research examines the reflections that university students valued regarding teaching and learning experiences during the Covid-19 Pandemic in the context of the degree programs at the National University of Patagonia San Juan Bosco (UNPSJB). The research team specifically asked, "What were the teaching practices that, as specific ’classroom’ situations turned into comprehensive support processes, and which students perceive as valuable and can be concretely recognized?" To address this, the authors worked with a category they termed "valuable experiences" as a way to explain which practices students considered significant in that context, both in terms of pedagogical approaches and social-emotional support practices.